Cell numbers contribute to cell fate during Ciona cardiopharyngeal mesoderm specification - Emily Singer; Haram Kim; Michael S. Levine; Nicholas Treen (Proceedings of the National Academy of Sciences, 2026)
The Ciona heart cell lineage can be accurately traced back to a pair of blastomeres, the B7.5 cells, that form at the 64-cell stage. In addition to the adult heart, the B7.5 cells also contribute to two tail muscle cells in the larva, as well as the muscles that form the siphons for pumping water for feeding. Because of the simplicity of this system, we have a good understanding of how the B7.5 derivatives are specified during development. However, we know less about how the Ciona embryo precisely regulates cell numbers, as well as what effects altering cell numbers will have on development. We found that cell numbers in the B7.5 lineage are controlled by a pulse of transcription of the cell cycle inhibitor Cdkn1.b . Cdkn1.b can be repressed by the paralogs Prdm1-r.a and Prdm1-r.b that are exclusively transcribed in the B7.5 cells at the 112-cell stage. We unexpectedly found that precocious arrest of cell division in the B7.5 cell lineage resulted in a reversion to tail muscle fate, even in cells that can migrate. Our work demonstrates an unexpected connection between the control of cell numbers and cell fate in development.